The chief data officer's playbook - Carruthers, Caroline; Jackson, Peter (London Facet Publishing, 2018)
"The new and rapidly expanding role of the chief data officer (CDO) is of significant interest and relevance to organisations and data professionals internationally. Written by two practicing CDOs, this new book offers a jargon-free, practical guide to making better decisions based on data. Content covered includes: why does any organisation need a CDO? the secret ingredients of the successful CDO; avoiding the hype cycle building the CDO team; who leads the technology? the CDO and data governance: enablement not red tape. This book will offer key insights and essential knowledge for CDOs looking to understand their position better; aspiring CDOs and data officers looking at career progression, those recruiting CDOs, and anyone else operating in the current data environment."--Back cover
Preface: the past two years -- Why does any organisation need a chief data officer? -- Secret ingredients of a chief data officer -- The first 100 days -- Delivering a data strategy in the cauldron of BAU -- Avoiding the hype cycle -- Relating to the rest of the business, especially the C-suite -- The chief data officer as a disruptor -- Building the chief data officer team -- The next 300 days -- The different generations of chief data officers -- What type of chief data officer are you? -- How to present yourself as a chief data officer -- Tinker, tailor, soldier, data ... -- The chief data officer and the technology -- The hoarding mentality and how to break it - - Data and information ethics -- The chief data officer and data governance -- The data revolution -- Advice to business owners, CEOs and the board -- Conclusion
Includes index.
Keywords: Data protection; Information technology -- Management -- Handbooks, manuals, etc; Knowledge management; Intellectual capital; Information technology -- Management; Technological innovations -- Management; Industrial management